2004
DOI: 10.1139/x03-193
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a cryopreserved gene bank of European elms

Abstract: Cryopreservation of a core collection of 444 elm (Ulmus spp.) clones in liquid nitrogen was carried out by two laboratories participating in a European project of conservation of elm genetic resources. Plant material, collected in nine European countries, represented a large sample of the genetic diversity within three European elm species and their hybrids. The cryopreservation technique used in both laboratories involved the stepwise freezing of cryotubes containing dormant buds. Comparisons with fresh buds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 16 publications
3
44
0
Order By: Relevance
“…The thorough analyses performed in course of more than 1 year showed that, despite a certain level of variability, several general features could be extracted, which confirm results of other plant collections (Garming et al 2009;Harvengt et al 2004). The main feature is the permanent character of field costs which remain constant over the years in contrast to the twostep character of costs in cryopreservation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The thorough analyses performed in course of more than 1 year showed that, despite a certain level of variability, several general features could be extracted, which confirm results of other plant collections (Garming et al 2009;Harvengt et al 2004). The main feature is the permanent character of field costs which remain constant over the years in contrast to the twostep character of costs in cryopreservation.…”
Section: Discussionsupporting
confidence: 79%
“…Cryopreservation was also subject of preliminary economical considerations in Germany and France (Harvengt et al 2004;Keller 2006;Schäfer-Menuhr et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…A cryopreserved core collection of European elms has been established successfully (18). The relatively small size of this core collection enables a logical and efficient characterization and evaluation in Japanese persimmon native to China.…”
Section: Discussionmentioning
confidence: 99%
“…In hardwoods, the cryopreservation of a collection of elm trees (Ulmus spp.) that had survived the epidemics of Dutch elm disease should be mentioned, as they are are potentially resistant to this disease [103,104].…”
Section: Long-term Preservation (Cryopreservation)mentioning
confidence: 99%